1999
DOI: 10.1016/s0020-7292(99)00117-4
|View full text |Cite
|
Sign up to set email alerts
|

A simple estimated fetal weight equation for fetuses between 24 and 34 weeks of gestation

Abstract: For estimating weights of preterm or low-birth weight fetuses of less than 2500 g, this simple equation appears to be clinically reliable and easy to use and suggests that previous normal ultrasonic fetal weight curves may underestimate or overestimate normal fetal delivery weight between the 24th and 34th week of gestation. Our formula approximates actual birth weight better and recommends Ott's ultrasonic weight curve for Iranian population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The fact that males have about 3% more birth weight at term than females [29] was discussed together with the question of the accuracy of fetal weight estimation in only two further studies: Mills et al [30] , investigating preterm pregnancies (weeks [23][24][25][26][27][28][29], had the same result as we state here, and Honarvar et al [31] reported a similar result investigating preterm pregnancies between weeks 24 and 34. There was no statistically significant difference of the birth weight between males and females though females had about 46 g more average birth weight.…”
Section: Discussionsupporting
confidence: 68%
“…The fact that males have about 3% more birth weight at term than females [29] was discussed together with the question of the accuracy of fetal weight estimation in only two further studies: Mills et al [30] , investigating preterm pregnancies (weeks [23][24][25][26][27][28][29], had the same result as we state here, and Honarvar et al [31] reported a similar result investigating preterm pregnancies between weeks 24 and 34. There was no statistically significant difference of the birth weight between males and females though females had about 46 g more average birth weight.…”
Section: Discussionsupporting
confidence: 68%
“…From 2004, gestational age has been routinely measured by a first trimester ultrasound scan. Records with missing information on gestational age and birthweight <1200 g ( n = 58) were included in the cohort by the calculated gestational age, assuming that the recorded birthweight was an average value . The interval between registered pregnancies was examined to ensure that double registration was not counted as recurrence.…”
Section: Methodsmentioning
confidence: 99%
“…Records with unregistered gestational age and birth weight <1,200 g (n=58) were included in the cohort by the calculated gestational age. 22 …”
Section: Methodsmentioning
confidence: 99%